Modelo teórico metodológico para el desarrollo de competencias genéricas desde el aprendizaje basado en retos (2024)
The purpose of this doctoral thesis is to generate a theoretical methodological model aimed at the development of generic competencies from Challenge-Based Learning, considering its foundations, dimensions and components that contribute to the comprehensive training of students, as a basis for improving the process. Of learning in higher education. The epistemological approach is the critical rationalist one, with a complementary mixed sequential multi-method paradigm. The research process is developed in four stages: theoretical in nature with the review of specialized literature and mainstream theories that support the study variables; stage of empirical nature where the necessary information is collected with the investigated actors, teachers and students of a selected higher education institution in Barranquilla in relation to learning based on challenges and generic competencies; analytical nature stage with which the processing and interpretation of data is developed, which shows that challenge-based learning (CBL) requires appropriate articulation with the external sector, didactic and evaluation strategies to solve real challenges, which implies direct and fluid articulation and communication between educational agents and the different training areas to recognize the reality of the context according to the application of knowledge in an interdisciplinary manner. And the purposeful stage with which the Reto Educa model and its INNOVAR methodology is configured with seven stages for its application with a view to the development of generic competencies, which was intersubjectively validated with national and international expert judges.